2021
DOI: 10.1111/1744-7917.12922
|View full text |Cite
|
Sign up to set email alerts
|

Knockin of the G275E mutation of the nicotinic acetylcholine receptor (nAChR) α6 confers high levels of resistance to spinosyns in Spodoptera exigua

Abstract: Spinosyns, including spinosad and spinetoram, act on the insect central nervous system, gradually paralyzing or destroying the target insect. Spinosad resistance is associated with loss‐of‐function mutations in the nicotinic acetylcholine receptor (nAChR) α6 subunit in a number of agricultural pests. Using gene editing, nAChR α6 has been verified as a target for spinosyns in five insect species. Recently, a point mutation (G275E) in exon 9 of nAChR α6 was identified in spinosad‐resistant strains of Thrips palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Therefore, if the presence of a particular nAChR subunit mutant can lead to decreased susceptibility to insecticides, such a mutant in the field population can potentially lead to an increased risk of cross‐resistance to these insecticides. For example, the G275E mutation of α6 increased the resistance of spinosyns in S. exigua , and the R81T mutation of β1 increased the resistance of imidacloprid and thiamethoxam in A. gossypii 26, 56 . Therefore, from the perspective of insecticide resistance management, it is important to avoid the rotation of insecticides that attack the same target site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the presence of a particular nAChR subunit mutant can lead to decreased susceptibility to insecticides, such a mutant in the field population can potentially lead to an increased risk of cross‐resistance to these insecticides. For example, the G275E mutation of α6 increased the resistance of spinosyns in S. exigua , and the R81T mutation of β1 increased the resistance of imidacloprid and thiamethoxam in A. gossypii 26, 56 . Therefore, from the perspective of insecticide resistance management, it is important to avoid the rotation of insecticides that attack the same target site.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the G275E mutation of ⊍6 increased the resistance of spinosyns in S. exigua, and the R81T mutation of ⊎1 increased the resistance of imidacloprid and thiamethoxam in A. gossypii. 26,56 Therefore, from the perspective of insecticide resistance management, it is important to avoid the rotation of insecticides that attack the same target site. It is important to highlight, however, that a degree of caution should be applied when extrapolating experimental findings, probably point mutants are more powerful tools in analyzing neonicotinoid mode of action than deletion mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The spinosyns including spinosad and spinoteram have been shown to act a population of nAChR that are not targeted by neonicotinoids, the binding site is also distinct to the orthosteric site [4]. The 6 subunit has been proposed as the main target of spinosyns since the resistance to spinosad in many insects is associated with loss-of-function mutations in the 6 gene [24], however, whether other subunits are involved is still unknown. We used spinoteram in bioassays and the results strongly indicated that spinosyns may specifically act on the 6 homomeric nAChR but not any other subtypes (Figure 4), which is consistent with a recent report using spinosad [25].…”
Section: Discussionmentioning
confidence: 99%
“…An essential pre-requisite for effective design of new insecticides targeting these receptors is an understanding of their distinctive binding properties. For many reasons, including low expression in endogenous tissues or difficulties in expressing insect receptors in heterologous systems, the characterisation of functional insect receptors has been challenging ( Perry et al, 2021 ; Zuo et al, 2022 ; Salgado, 2021 ). Even in the tractable D. melanogaster insect model, there has been no systematic isolation of mutations in nAChR subunit genes, until recently, when Perry and colleagues described the generation of a new set of null mutations in nine out of the ten D. melanogaster subunit genes ( Perry et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%